AN ANALYSIS OF NETWORK ON THE DEVELOPMENT OF PT. JINGGA PROPERTI HOUSES IN SIGI BIROMARU - Suerni, Endang; Kaseng, Saharuddin; Syamsuddin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
Project management is used to plan, implement, and control project activities to minimize risks to project time and cost. Completion of an infrastructure project on time is a top priority. One of the problems that often occurs is the time delay of the project caused by the incompatibility of the schedule planning with the character of human resources, building materials, disasters, company regulations that can result in construction failure and have an impact on costs. Type of the research was descriptive quantitative, quantitative, and qualitative data sources. Planning for the construction of subsidized type 36 houses using Gant cart takes 75.5 days/604.5 hours in the construction of 1 unit of subsidized housing. This study aims to determine and analyze the network of construction of subsidized type 36 houses at PT. Jingga Properti Indonesia in Kalukubula Sigi Biromaru using the PERT (Project Evaluation Review Technique) method both in manual calculations and the assistance of POM-QM Software, the results of the research obtained that the construction of subsidized type 36 houses at PT. Jingga Property Indonesia can be completed in 400.47 hours. The results of the realization of house construction before the calculation using the PERT method were 538 hours. If targeted for 420 hours, the possibility of completion is 99%. The proposed schedule of 294.52 hours can be realized if the masons are added/more activities are done simultaneously.